The Incredible Presentation of Malaria: A Case Series - Razzaque, SMA (Ibrahim Cardiac Medical Journal, 2023)
Background & Objective: Man and malaria seem to have evolved together. Malaria has always been the subject of research for medical practitioners from time immemorial. Malaria is known for its fever paroxysm, starting with chills, rigors, high grade fever, followed by sweating as the fever declines. However, this classical pattern may not be seen in many patients and frequently manifest as a non-specific illness. Quite often patients do not experience the classic intermittent fever with chills and rigors, while some may do not experience fever at all. Rather they may have a wide spectrum of non-specific symptoms that may mimic other systemic illnesses. So, the consulting physicians must judiciously consider malaria as a diagnostic possibility in an array of probable diagnoses. As the morbidity and mortality of severe malaria are very high, one must not wait for the characteristic paroxysmal fever to ask for a malaria test, with a potential risk of developing fatal malaria. The present study describes a case series of malaria with a myriad of atypical presentations which may sensitize the physicians about abnormal presentations of malaria in our population and aid in early diagnosis and management of the potentially fatal cases of malaria. Ibrahim Card Med J 2021; 11 (2): 16-26